USING ANIMAL CARTOON PICTURE ON WRITING NARRATIVE TEXT TO IMPROVE THE STUDENTS ABILITY AT MTSN 2 MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2022)
This study aims to know how effectiveness using animal cartoon picture on writing narrative text to improve the ability of students. This research used a quantitative method. Analyzed with Pre-Experimental one-group design. The result indicated that the students’ average score in writing narrative text before being taught with animal cartoon picture was 14.35 and after being taught with animal cartoon picture was 18.20. The indicated based on the output data of paired sample test it is discovered the Sig. (2-tailed) is 0.000. It means that the significance level is less than 0.05 (0.000 < 0.05). Means the alternative hypothesis (Ha) is accepted, while the null hypothesis (Ho) is rejected. It could be concluded that there is significant different of mean score of the students’ writing narrative text with animal cartoon picture for the third grade students at MTsN 02 Makassar before and after teaching treatment in the classroom. Otherwise, animal cartoon picture can be applied as an alternative to teach writing especially about narrative text for the third grade students at junior high school